A Study of the Thematic Interpretation of Wahbah Az-Zuhaili on Magic and Santet Verses in the Socio-Religious Context in Indonesia - Prabowo, Arrahman Aji; Yuslem, Nawir (QiST: Journal of Quran and Tafseer Studies, 2025)
This study aims to examine Wahbah Az-Zuhaili's views on the practice of magic and black magic in Islam as explained in Tafsir al-Munir. Using qualitative methods with tahlili and descriptive-analytical approaches, this study analyzes three main verses: Surah Al-Baqarah: 102, Al-Falaq: 4, and Thaha: 66-70. The research process was carried out through a literature study of the interpretation text, complemented by a comparison with classical literature and contextualization of black magic practices in Indonesia. The results of the study indicate that black magic is a form of deviation from the faith that can lead to disbelief, while black magic is categorized as a branch of black magic because it contains elements of manipulation through supernatural media. Az-Zuhaili emphasized that black magic is a major sin that deserves severe legal sanctions. The mitigation strategies offered include strengthening monotheism, ruqyah syar'iyyah, and Islamic education as preventive measures. This research emphasizes the importance of Tafsir al-Munir as a reference for contemporary interpretation that is not only normative but also responsive to modern socio-religious challenges. The novelty of this research lies in the integration of tafsir, fiqh, and the local Indonesian context in explaining magic and witchcraft in an applied manner.